The family next door : the heartbreaking imprisonment of the thirteen Turpin siblings and their extraordinary rescue - Glatt, John (St. Martin's Press, 2019)
"On January 14, 2018, a seventeen-year-old girl climbed out of the window of her Perris, California home and dialed 911 on a borrowed cell phone. Struggling to stay calm, she told the operator that she and her 12 siblings--ranging in age from 2 to 29--were being abused by their parents. When the dispatcher asked for her address, the girl hesitated. 'I've never been out,' she stammered. To their family, neighbors, and online friends, Louise and David Turpin presented a picture of domestic bliss: dressing their thirteen children in matching outfits and buying them expensive gifts. But what police discovered when they entered the Turpin family home would eclipse the most shocking child abuse cases in history. For years, David and Louise had kept their children in increasing isolation, trapping them in a sinister world of torture, fear, and near starvation."--